Multiplexed Detection: Precisely Encoded Barcodes through the Structure‐Fluorescence Combinational Strategy: A Flexible, Robust, and Versatile Multiplexed Biodetection Platform with Ultrahigh Encoding Capacities (Small 19/2021). Issue 19 (12th May 2021) - Wang, Yao; Chen, Cang; He, Jing; Cao, Yimei; Fang, Xiaoxia; Chi, Xiaomei; Yi, Jingwei; Wu, Jiancong; Guo, Qingsheng; Masoomi, Hajar; Wu, Chongzhao; Ye, Jian; et al.
Abstract : In article number 2100315, Hong Xu and co‐workers develop a huge barcode library containing 300 kinds of encoded microbeads through a novel structure‐fluorescence combinational strategy. These barcodes similar to celestial bodies in the starry sky could be excited by a single laser to achieve the decoding of three elements, including structure and two fluorescence information. The barcodes platform exhibits the great promising potential for actual multiplexed biodetection.